Characterization of electrolyte content in urine samples through a differential microfluidic sensor based on dumbbell-shaped defected ground structures. Issue 9 (27th November 2020) - Muñoz-Enano, J.; Vélez, P.; Gil, M.; Jose-Cunilleras, E.; Bassols, A.; Martín, F.
Abstract: In this paper, a differential microfluidic sensor and comparator based on a pair of microstrip lines loaded with dumbbell-shaped defected ground structure resonators is applied to the characterization of electrolyte concentration in samples of horse urine. Since variations in the total electrolyte content in urine may be indicative of certain pathologies, the interest is to use the device as a comparator, in order to determine changes in the electrolyte concentration as compared to a reference level. To validate the approach, we have made differential measurements of a set of urine samples with different electrolyte concentrations (which have been previously obtained by means of electrochemical methods). The obtained results correlate with the nominal electrolyte concentrations of the samples, thereby pointing out the potential of the approach as a low-cost pre-screening method (or complementary diagnosis system) to detect potential pathologies or diseases in horses and other animals.